Nurturing adaptation capacities in Chin highlands Lessons from Sakta: A Climate Smart Village in Myanmar - Barbon, Wilson John; Myae, Chan; Su, Myat Noe; Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
This primer showcases the lessons learned from implementing climate-smart agriculture in Sakta village in Chin State, Myanmar. Sakta village is one of the Climate-Smart Village project sites operated by the International Institute of Rural Reconstruction (IIRR) and Karuna Mission Social Solidarity (KMSS Hakha).